Building an Academic Writing Culture As a Medium to Improve Students’ Self-Efficacy - Rahmadi Nirwanto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the relationship between academic writing culture and students' self-efficacy. Academic writing is a crucial skill in higher education, yet many students struggle to develop effective writing habits. Low interest, lack of academic support, and limited foundational writing skills are key factors affecting the students' self-efficacy in performing academic tasks. Methodology: This study employed a quantitative approach with a correlational method. A purposive sampling technique was used to select 26 students who were actively engaged in academic writing. Data were collected through a Likert-scale closed questionnaire and analyzed using the Pearson product-moment correlation to determine the strength and direction of the relationship between academic writing culture and self-efficacy. Main Findings: The results indicate a very strong relationship between academic writing culture and students' self-efficacy, with a correlation coefficient (r) of 0.994. The coefficient of determination (R²) of 98.8% demonstrates that academic writing culture makes a significant contribution to improving students' self-efficacy, while other factors influence 1.2%. This finding suggests that fostering a strong academic writing culture enhances students' confidence in facing academic challenges. Novelty/Originality of this Study: This study provides novel insights by highlighting the essential role of academic writing culture as a dominant factor influencing students' self-efficacy. While previous research has examined writing difficulties and self-efficacy separately, this study establishes a direct and strong correlation between them. The findings underscore the importance of institutional support in promoting academic writing habits that boost students' confidence and academic success.